Ultrasound-detected gastric changes related to zolbetuximab-induced emesis: a case series - Harada, Kazuaki; Ishida, Koichi; Kaneko, Shiho; Yokoyama, Tatsuya; Sawaguchi, Shintaro; Nakamura, Takeaki; Kawamoto, Yasuyuki; Yuki, Satoshi; Nishida, Mutsumi; Sakamoto, Naoya; Komatsu, Yoshito (Frontiers in Oncology, 2025)
BackgroundZolbetuximab prolongs survival in patients with claudin18.2 (CLDN18.2)-positive gastric cancer (GC) and gastroesophageal junction cancer. However, it is associated with an increased risk of emesis, and its underlying mechanism remains unclear.Case PresentationThis report presents three cases of advanced GC that underwent abdominal ultrasonography (US) during zolbetuximab administration. In two patients with primary gastric lesions, severe nausea occurred during the first treatment cycle. US findings revealed increased echogenicity of the submucosal layer, enhanced layer stratification, and increased blood flow signals, which improved as the emesis subsided. During the second cycle, emesis was milder, and US findings revealed only slight changes. In the third patient who underwent total gastrectomy, no nausea or abnormal US findings were observed.ConclusionThese US findings indicate gastric tumor tissue injury due to zolbetuximab, which is associated with emesis. US is a valuable tool for further elucidating the mechanisms underlying zolbetuximab-induced emesis and may also contribute to the prediction and prevention of this adverse event.StatementZolbetuximab treatment has been reported to improve survival in patients with HER2-negative, CLDN18.2-positive advanced, unresectable, or recurrent gastric and gastroesophageal junction cancers. However, it is associated with a high incidence of nausea, particularly during the first infusion, and the underlying mechanism remains unclear. We present three cases of advanced or recurrent gastric cancer treated with zolbetuximab, during which abdominal ultrasonography (US) was performed. In two cases with primary gastric tumors, US revealed characteristic changes in the gastric wall at the onset of nausea, suggestive of edema and inflammation. These changes appeared prior to the symptoms and resolved as nausea improved. Nausea during the second infusion was milder, with less pronounced US changes. The third case includes a patient who had undergone total gastrectomy; the patient did not experience nausea, and no gastrointestinal changes were observed on US. This is the first report to describe US findings associated with zolbetuximab-induced nausea. These observations suggest that gastric wall changes detectable using US are closely linked to nausea and may reflect underlying gastric injury. This report also highlights the potential of bedside US monitoring to help predict and prevent nausea during zolbetuximab therapy.